Descrição e analise das trajetórias políticas, dos discursos e da atuação das vereadoras da legislatura 2013/2016 do município de Guaíra - Paraná - Hansel, Tiago Fernando (2016)
This Master s thesis has the objective of identifying and analyzing the political path, speeches and performance of councilwomen during 2013/2016 legislature in Guaira municipality in Parana State (Brazil). The bibliographical source of this research is composed by authors Céli Regina Jardim Pinto, Clara Maria Araújo and Luís Felipe Miguel, contemporary researchers, who provided the foundation for this thesis. The protagonists of this study are councilwomen Franciele de Lima Danelon, Miriam Caleste dos Santos, Rosana de Lima Brizzi and Tereza Camilo dos Santos. The study is divided in four parts, the first being a discussion on women in politics among the authors described above, the second part is a brief historical approach of women in Guaira chamber, then the presentation and analysis of the speeches of the women councilors at the tribune and their acts as council members, and, finally, the analysis of the speeches of women councilors about the interview conducted with them, observing the statements and contradictions with the material previously collected. The data analysis shows significant differences among these women, ranging from personal information, through political career down to the mode of operation.